MAIN PARAMETER ANALYSIS AND MECHANICAL BEHAVIOR OF ANTI-KAGOME LATTICE STRUCTURE - HAN ZongZheng; DUAN MingDe; YANG ZiWei; ZHANG ZhuangYa; WANG Pei; WANG MaoHua (Jixie qiangdu)
In order to seek a lattice structure with better mechanical properties, a reverse Kagome lattice unit cell model is proposed based on the point group theory, and it is contrastively analyzed with the kagome unit cell model in the mechanical properties. The stress and strain theory is used to determine the key parameter of the reverse Kagome unit cell, which is the range of the inclination angle ω on the constraint condition of realizing the compression performance, shearing property and reaching the relative density and bearing capacity of the reverse Kagome. Combined with the finite element analyze results, it can determine the value of ω of this model under the best mechanical performance. An experiment of the reverse Kagome lattice model is performed to verify the correctness of the theoretical analysis. The research shows that when the tilt angle ω is 52°, the reverse Kagome lattice structure has the best compression resistance, and when the tilt angle ω is 38°, the shear performance of this structure is better; In terms of overall performance, the 45°inclination angle is better than the other two inclination angles.